Open mitral valvotomy: fourteen years' experience. Issue 1 (July 1983) - Kay, P H; Belcher, P; Dawkins, K; Lennox, S C
Abstract : During the period 1968 to 1980, 222 patients with mitral valve disease in which stenosis was the dominant lesion were admitted under the care of the senior author. All patients presented with severe dyspnoea (NYHA grades 3 or 4). One hundred and fifty seven (71%) patients were treated by open mitral valvotomy. One patient died within 30 days of operation (0.6% hospital mortality) and one suffered a transient cerebrovascular accident. One hundred and twenty four (70%) patients were followed up for one to 14 years (mean 7.5 years). There were seven late deaths. Actuarial curves predict the 90.2% 10 year survival after open mitral valvotomy. Eight patients required mitral valve replacement for restenosis corresponding to 16% at 10 years. The remaining patients are in NYHA grades 1 and 2.